PENERAPAN MODEL GAME-BASED LEARNING BERBASIS MEDIA DIGITAL EDUCANDY UNTUK MENINGKATKAN HASIL BELAJAR BAHASA INGGRIS SISWA KELAS IV UPTD SDN 4 AMARANG KABUPATEN MAROS - Indah Dwi Anugrah S.; Nurhaedah Nurhaedah; Syamsuryani Eka Putri Atjo (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aimed to improve the English learning outcomes of fourth-grade students at UPTD SDN 4 Amarang through the implementation of the Game-Based Learning (GBL) model supported by the Educandy digital media. This study employed Classroom Action Research (CAR) using a mixed-methods approach. The participants consisted of 20 fourth-grade students. The research was conducted in two cycles, each comprising the stages of planning, implementation, observation, and reflection. Data were collected through classroom observations, interviews, and learning achievement tests. The findings revealed improvements in both teacher and student activities, progressing from fair/low categories to a good category. In addition, students' cognitive learning outcomes increased significantly, with classical learning mastery reaching 90% by the end of Cycle II. It can be concluded that the implementation of the Game-Based Learning (GBL) model supported by Educandy digital media was effective in improving students' English learning outcomes.